2003
DOI: 10.1002/jmv.10479
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of HPV 16 in South African women with cancer of the cervix and cervical intraepithelial neoplasia

Abstract: Despite the high prevalence of cervical cancer and cervical neoplasias in South Africa, few studies have been performed in this region to establish which human papillomavirus (HPV) types are associated with the development of high-grade cervical intraepithelial neoplasia lesions and cervical cancer. To investigate these prevalence rates, punch biopsies were obtained from 56 women with cervical cancer and 141 women with histologically diagnosed cervical intraepithelial neoplasia 2 or 3 lesions. Nested polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
37
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 20 publications
7
37
1
Order By: Relevance
“…Previous studies have reported a high prevalence of multiple HPV infections among HIV-infected women (Palefsky et al, 1999;Gravitt et al, 2002) which is associated with an increased risk of intraepithelial neoplasia and of cancer (Moscicki et al, 2004a;Herrero et al, 2005). As was found in other African studies (Ter Meulen et al, 1992;Chabaud et al, 1996;La Ruche et al, 1998;Bayo et al, 2002;Kay et al, 2003), HPV-16 and -18 were less common than other HR-HPV types overall, but they were involved in 64% of HSIL lesions, while 93% of women with HSIL had viruses related to the HPV-16 or HPV-18 phylogenetic groups. Therefore, administration of a bivalent HPV-16/18 vaccine in this population before they get exposed might have the potential to prevent the majority of highgrade lesions in this population, but this would need to be determined in prospective studies.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have reported a high prevalence of multiple HPV infections among HIV-infected women (Palefsky et al, 1999;Gravitt et al, 2002) which is associated with an increased risk of intraepithelial neoplasia and of cancer (Moscicki et al, 2004a;Herrero et al, 2005). As was found in other African studies (Ter Meulen et al, 1992;Chabaud et al, 1996;La Ruche et al, 1998;Bayo et al, 2002;Kay et al, 2003), HPV-16 and -18 were less common than other HR-HPV types overall, but they were involved in 64% of HSIL lesions, while 93% of women with HSIL had viruses related to the HPV-16 or HPV-18 phylogenetic groups. Therefore, administration of a bivalent HPV-16/18 vaccine in this population before they get exposed might have the potential to prevent the majority of highgrade lesions in this population, but this would need to be determined in prospective studies.…”
Section: Discussionsupporting
confidence: 51%
“…The increased prevalence of HPV18 in cervical cancer compared to CIN2/3 as found in our study is in agreement with a recent meta-analysis and data from Australia, South Africa and the US (Clifford et al, 2003;Kay et al, 2003;Zuna et al, 2004). The sample size of our study was slightly low, because CIN2/3 and SCC cases were collected from one restricted geographical area.…”
Section: Discussionsupporting
confidence: 93%
“…However, the most prevalent genotypes in HSILs were HPV-35 followed by 58 and 66, which differ from a previous study conducted in South Africa by Kay et al, in Cape Town, and other studies, where the most prevalent genotypes in HSILs were HPV-16 and 18. 8,4,9 This difference could represent regional variations and differences in the populations studied. The present study population was women participating in a vaginal microbicide study, who were women from the community without any specific risk factors other than the high HIV prevalence in this community, which was reported to be 25%.…”
Section: Discussionmentioning
confidence: 99%